Anti-MDA5 Antibody-Positive Dermatomyositis Presenting with Cellulitis-Like Erythema on the Mandible as an Initial Symptom - Yuki Hattori; Kanako Matsuyama; Tomoko Takahashi; En Shu; Hiroyuki Kanoh; Mariko Seishima (Karger Publishers, 2018)
Panniculitis is an uncommon skin eruption observed in patients with dermatomyositis (DM)/clinically amyopathic dermatomyositis (CADM), especially in anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive DM. We present here a 51-year-old Japanese woman with an anti-MDA5 antibody-positive DM who initially had cellulitis-like erythema on her right mandible. Histopathological findings showed a subcutaneous lobular infiltration of lymphocytes. The patient developed typical skin eruptions of DM/CADM, rapidly progressive interstitial lung disease, and severe muscle weakness 2 weeks after the first visit. After the diagnosis of anti-MDA5 antibody-positive DM, she was treated with intravenous steroid pulse therapy (methylprednisolone, 1,000 mg/day for 3 days), oral prednisolone at 1.0 mg/kg/day, and tacrolimus at 4.0 mg/day. The lesions of panniculitis associated with DM/CADM typically present on the buttocks, thighs, arms, and abdomen. This is the first DM/CADM case with localized panniculitis on the face. Panniculitis and myositis usually show simultaneous improvement during treatment. Although panniculitis disappeared with steroid and tacrolimus treatment and did not recur, muscle weakness was intractable and recurred in this case. This indicates that the clinical courses of panniculitis and myositis of DM/CADM do not always change in parallel.